Integrated Stunting Reduction Model through Supplementary Feeding and Deworming: A Cross-Sectional SEM-PLS Study among Toddlers - Wardita, Yulia; Kurniyati, Eka Meiri; Permatasari, Dian (International Journal of Health Concord, 2025)
Background: Stunting remains a major public health problem in coastal areas of Sumenep Regency, Indonesia, with a prevalence of 21.6%, exceeding the provincial average. Government programs such as supplementary feeding (PMT) and deworming have been widely implemented; however, evidence regarding how these interventions interact with maternal characteristics to influence stunting outcomes in coastal populations remains limited. Therefore, an integrated analytical model is needed to clarify the direct and indirect pathways influencing stunting among toddlers in coastal settings Methods: This analytical observational study employed a cross-sectional design and followed the STROBE guideline for cross-sectional studies. The study was conducted from March to September 2025 in two coastal sub-districts of Sumenep Regency (Batang-batang and Dungkek). A total of 352 mothers with toddlers were selected using stratified random sampling. Inclusion criteria were mothers with children under five years of age who were not suffering from severe illness and consented to participate, while exclusion criteria included absenteeism during data collection. Independent variables included maternal education, maternal knowledge, child sex, child age, supplementary feeding, deworming, and exclusive breastfeeding, while the dependent variable was stunting incidence. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 4, applying a significance level of 5%. Result: SEM-PLS analysis showed that supplementary feeding had the strongest direct effect on stunting incidence (β = 0.438; t = 11.173; p < 0.001). Deworming (β = 0.111; t = 2.925; p = 0.004) and maternal education (β = 0.457; t = 11.480; p < 0.001) also had significant direct effects. Maternal education indirectly influenced stunting through supplementary feeding and deworming pathways, while maternal knowledge influenced exclusive breastfeeding but did not show an indirect association with stunting. A total of nine significant structural paths were retained in the final model. Conclusion: Supplementary feeding is the most influential intervention in reducing stunting among toddlers in coastal areas, supported by deworming and maternal education. An integrated stunting reduction strategy combining regular supplementary feeding, routine deworming, and maternal education strengthening is recommended, particularly for vulnerable coastal populations. These findings provide a clear evidence-based framework to optimize program convergence for stunting prevention.